FMF50: a score for assessing outcome in familial Mediterranean fever. Issue 5 (25th February 2014) - Ozen, Seza; Demirkaya, Erkan; Duzova, Ali; Erdogan, Ozlem; Erken, Eren; Gul, Ahmet; Kasapcopur, Ozgur; Kasifoglu, Timucin; Kisacik, Bunyamin; Ozdogan, Huri; Tunca, Mehmet; Acikel, Cengizhan; et al.
Abstract : Background: Colchicine is the main treatment for familial Mediterranean fever (FMF). However, biological agents and other treatments are available for patients who are unable to receive optimal treatment. Objective: To develop outcome criteria that define response to treatment. Methods: Two rounds of Delphi exercise were followed by a consensus conference enabling the definition of the criteria to be employed. Data for patients with FMF responding and resistant to their treatment were obtained from the FMF Arthritis Vasculitis and Orphan disease Research in paediatric rheumatology (FAVOR) website. The suggested criteria were analysed and validated in this patient cohort. Sensitivity/specificity measures and the ability of the score to discriminate between patients with active and inactive disease via the best cut-off score were calculated by a receiver operating characteristic analysis. Results: Compliance with the maximum dose of the drug was considered essential for evaluation of the patients. Seven criteria were suggested in the consensus conference. The performance of each criterion, in differentiating between resistant and responsive patients, was tested. The final set of criteria was defined as at least 50% improvement in five of six criteria, without worsening in any one defined response to treatment with a very high sensitivity and specificity. The items of this FMF50 included: 1. Percentage change in the frequency of attacks with the treatment. 2. Percentage change in the duration of attacks with the treatment. 3. Patients/parents' global assessment of disease severity (10 cm visual analogue scale (VAS)). 4. Physicians' global assessment of disease severity (10 cm VAS). 5. Percentage change in arthritis attacks with the treatment. 6. Percentage change in C-reactive protein, erythrocyte sedimentation rate or serum amyloid A level with the treatment. Conclusions: The FMF50 produced is a user-friendly measurement tool to guide physicians and can be used in clinical trials.